Knowledge, attitude and practice of health care workers on solid medical waste management in two urban hospitals of Bangladesh: a mixed-method study - Md Tauhidul Islam; Md Abdur Rafi; Mohammad Jahid Hasan (Journal of Health, Population and Nutrition)
Abstract Background Proper management of solid medical waste is a crucial component of an efficient healthcare system. The objective of the present study was to assess the knowledge, attitude, and practices of medical waste management among the healthcare workers of two selected hospitals of Dhaka city of Bangladesh. Methods This cross-sectional, mixed-method study was conducted in two tertiary care hospitals of Dhaka, Bangladesh–icddr, b Dhaka hospital (Private) and Dhaka Shishu hospital (Public) during November, 2011. A number of 138 healthcare professionals (29 doctors, 80 nurses and 29 cleaners) participated in the study. The study had three parts of data collection: (i) survey with health care workers to determine their knowledge, attitudes, and practices about medical waste management; (ii) in-depth interviews with health officials of infection control committee; and (iii) observation using a facility checklist to determine the current practice of medical waste management. Results Overall, participants from IDH had better knowledge, and practice regarding solid medical waste management compared to DSH. Doctors of IDH demonstrated better knowledge regarding the responsible person for waste management and a better attitude regarding the statement that it was a teamwork (p-value < 0.05). Similarly, nurses and cleaners of IDH showed superior level of knowledge of waste handling as well as safer practices, including consistent use of personal protective equipment. Workers of DSH reported higher incidence of errors and sharp injuries also. From the observation, it was found that IDH authority was more likely to follow the waste management guideline. Poor knowledge and attitude were the major barriers for proper waste management in IDH while lack of funds, human resource and logistics were the major barriers in DSH. Conclusions Both hospitals, particularly DSH, demonstrated significant deficiencies in knowledge, attitude, and practice of proper solid medical waste management. Despite limitations, IDH, exhibited more efficient waste management procedures.